Segmental cytomegalovirus colitis mimicking sigmoid tumor in an immunocompetent patient - Carlos Cerdán Santacruz; Patricia Sáez Carlin; Rocío Santos Rancaño; Luis Ortega Medina; Javier Cerdán Miguel (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Cerdán Santacruz C, Sáez Carlin P, Santos Rancaño R, Ortega Medina L, Cerdán Miguel J. Segmental cytomegalovirus colitis mimicking sigmoid tumor in an immunocompetent patient. Turk J Gastroenterol 2019; 30(10): 932-4.